Nanofiber sheet

JP2023177928A5Inactive Publication Date: 2025-03-13KAO CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2022090901
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2022-06-03
Publication Date
2025-03-13
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Nanofiber sheets face challenges in maintaining good transferability and conformability to the skin, particularly under high temperature or high humidity conditions, with existing solutions either compromising on adhesion or dissolving due to moisture absorption.

Method used

A nanofiber sheet design incorporating a base layer and a nanofiber layer composed of specific polymers with controlled moisture absorption, where the nanofiber layer includes a first polymer with 1% or less moisture absorption and a second polymer with more than 1% but less than 40% absorption, blended in a specific ratio, to enhance transferability and conformability.

Benefits of technology

The nanofiber sheet maintains excellent transferability and conformability even under high temperature or high humidity conditions, ensuring stable adhesion and effective skin protection, while reducing the risk of dissolution and improving moisture resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000000_0000_ABST
    Figure 00000000_0000_ABST
Patent Text Reader

Abstract

To provide a nanofiber sheet having a nanofiber layer excellent in transferability with good skin compatibility, a skin protection kit using the nanofiber sheet and a manufacturing method of the nanofiber sheet.SOLUTION: A nanofiber sheet includes a substrate layer and a nanofiber layer. The nanofiber sheet is used with the substrate layer removed in time of use and the nanofiber layer adhered onto an adhesion object portion. The nanofiber layer is arranged on one side of the substrate layer. The nanofiber layer includes: a first polymer having a moisture absorption degree of 1% or less under a high-temperature high-humidity environment (standing for 24 hours at 40°C and 90 RH%); and a second polymer having a moisture absorption degree over 1% to 40% or less under a high-temperature high-humidity environment (standing for 24 hours at 40°C and 90 RH%).SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] The present invention relates to a nanofiber sheet having a nanofiber layer, a skin protection kit, and a method for producing a nanofiber sheet. [Background technology]

[0002] A nanofiber sheet comprising a substrate layer and a nanofiber layer laminated together is known (see, for example, Patent Document 1). When using the nanofiber sheet, the nanofiber layer is attached to a target site, such as human skin, while supported by the substrate layer, and then the substrate layer is removed, transferring the nanofiber layer to the target site. The nanofiber layer utilizes its capillary force to retain preparations, such as beauty serums and moisturizers, between the fibers. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] Japanese Patent Application Laid-Open No. 2012-12716 Summary of the Invention [Problem to be solved by the invention]

[0004] There is a demand for a nanofiber sheet in which the nanofiber layer is easily transferred to the skin and which has a good compatibility with the skin. In nanofiber sheets, when the nanofiber layer is formed using only a water-insoluble polymer compound, transferability is good, but the nanofiber layer tends to have poor skin compatibility. On the other hand, when a nanofiber sheet is made by incorporating a water-soluble polymer compound into the nanofiber layer to improve skin compatibility, compatibility is improved, but the nanofiber layer absorbs moisture, dissolves, and adheres to the base layer, making transfer difficult. Furthermore, such dissolution of the nanofiber layer tends to occur particularly easily under conditions of high temperature or high humidity, leaving room for improvement in nanofiber sheets.

[0005] The present invention relates to a nanofiber sheet that has excellent transferability and good compatibility even when stored under conditions such as high temperature or high humidity, a skin protection kit using the nanofiber sheet, and a method for producing the nanofiber sheet. [Means for solving the problem]

[0006] A nanofiber sheet according to one embodiment of the present invention includes a substrate layer and a nanofiber layer. When the nanofiber sheet is used, the base layer is peeled off and the nanofiber layer is attached to a target site. The nanofiber layer is disposed on one surface of the substrate layer. The nanofiber layer is a first polymer having a moisture absorption rate of 1% or less when left standing in a high temperature and high humidity environment (40°C, 90% RH for 24 hours); The second polymer has a moisture absorption rate of more than 1% and less than 40% when placed in a high-temperature, high-humidity environment (40°C, 90% RH for 24 hours). Includes.

[0007] A skin protection kit according to one embodiment of the present invention includes the nanofiber sheet and a preparation. When using the nanofiber sheet, the preparation is applied to the target site before or after the nanofiber layer is attached to the skin.

[0008] A method for manufacturing a nanofiber sheet according to one embodiment of the present invention comprises a base layer and a nanofiber layer disposed on one side of the base layer, and the base layer is peeled off during use, and the nanofiber layer is attached to a target area for attachment. The method for producing the nanofiber sheet includes a step of applying a nanofiber layer-forming composition to one surface of the base layer by electrospinning to form the nanofiber layer. The nanofiber layer-forming composition is a first polymer having a moisture absorption rate of 1% or less when left standing in a high temperature and high humidity environment (40°C, 90% RH for 24 hours); a second polymer whose moisture absorption rate in a high temperature and humidity environment (left to stand for 24 hours at 40°C and 90% RH) is more than 1% and not more than 40%; One or more selected from monohydric alcohols and ketones Includes. [Effects of the Invention]

[0009] The nanofiber sheet of the present invention has excellent transferability and good compatibility even when stored under conditions of high temperature or high humidity. [Brief explanation of the drawings]

[0010] [Figure 1] 1 is a plan view of a nanofiber sheet according to one embodiment of the present invention. [Figure 2] 1 is a schematic diagram showing the configuration of a skin protection kit according to one embodiment of the present invention. [Figure 3] FIG. 1 is a schematic diagram of an apparatus used to manufacture a nanofiber sheet according to one embodiment of the present invention, showing how nanofibers are deposited on a substrate layer to form a nanofiber layer. [Figure 4] 1 is a graph showing the relationship between the proportion of the second polymer in the nanofiber layer and the overall average usability score of the nanofiber sheet after storage at high temperature and humidity. DETAILED DESCRIPTION OF THE INVENTION

[0011] The present invention will be described below based on preferred embodiments thereof.

[0012] <Overall structure of nanofiber sheet> As shown in Fig. 1, the nanofiber sheet 1 of the present invention comprises a base layer 2 and a nanofiber layer 3 disposed on one surface, or lamination surface 2a, of the base layer 2. When using the nanofiber sheet 1, the base layer 2 is peeled off and the nanofiber layer 3 is attached to the target site, human skin. In the nanofiber sheet 1, the nanofiber layer 3 is preferably laminated directly on the base layer 2, but another layer (hereinafter referred to as the first layer) may be provided between the nanofiber layer 3 and the base layer 2 as long as it does not impair the effects of the present invention. In this configuration, when the nanofiber layer 3 is transferred to the attachment target site, the first layer may be transferred to the attachment target site together with the nanofiber layer 3, or the first layer may remain on the base layer 2 and only the nanofiber layer 3 may be transferred to the attachment target site. Furthermore, within the scope of not impairing the effects of the present invention, another layer (hereinafter referred to as the second layer) may be provided on the surface (hereinafter referred to as the front surface) of the nanofiber layer 3 of the nanofiber sheet 1 opposite the surface facing the base layer 2. In this configuration, for example, the second layer may be configured to function as a protective sheet that protects the nanofiber layer 3 during storage of the nanofiber sheet 1, thereby further improving the film quality stability of the nanofiber layer 3. In this case, when transferring the nanofiber layer 3 to the attachment target site, the second layer functioning as the protective sheet may be peeled off to expose the surface of the nanofiber layer 3, and then the nanofiber layer 3 may be transferred. Furthermore, the second layer may be configured to be transferred to the attachment target site together with the nanofiber layer 3 during transfer. In this case, the nanofiber layer 3 is positioned above the attachment target site via the second layer. In such a configuration, for example, by configuring the second layer to have the function of a formulation, as described below, the process of applying the formulation, as described below, can be reduced, thereby improving the convenience of the nanofiber sheet 1. In addition, the nanofiber sheet 1 may have either the first layer or the second layer, or may have both. In the following description, a nanofiber sheet 1 in which the first and second layers are not provided and the nanofiber layer 3 is laminated directly on the base layer 2 will be described as an example.

[0013] When using the nanofiber sheet 1, the base layer 2 is peeled off, and one surface of the nanofiber layer 3 is attached to the target site, human skin. The nanofiber layer 3 of the present invention is suitable for use in treating wounds and abnormal conditions from the skin surface to the basal layer of the epidermis. Specifically, it is suitable for improving skin conditions and wound healing, with the objectives of promoting tissue regeneration, promoting basement membrane regeneration, activating epidermal cell proliferation, epithelialization (promoting keratinization), improving barrier function, improving moisture content, reducing scale, inhibiting crust formation, suppressing inflammation, and inhibiting post-inflammatory pigmentation. The nanofiber layer 3 is transferred to the target site for wound healing, such as human skin suffering from symptoms such as scales and inflammation or damaged skin after laser treatment, to protect the skin. The nanofiber layer 3 attached to the skin not only protects the skin from external stimuli and foreign substances, but also efficiently heals symptoms such as scales and inflammation and damage after laser treatment. The target site to which the nanofiber layer 3 of the nanofiber sheet 1 is transferred is typically human skin, but is not limited to this. For example, it can be attached to human teeth and gums, the skin, teeth, and gums of non-human mammals, or the surfaces of plants such as branches and leaves. The following explanation will be given taking the example of attachment to human skin.

[0014] The nanofiber sheet 1 of the present invention is preferably used in combination with a formulation (described below). By using the formulation in combination, the capillary force of the nanofiber layer can be utilized to retain the formulation between the fibers. This allows the formulation to act efficiently and effectively on the skin while protecting the skin. The nanofiber layer 3 may be used alone without being used in combination with a preparation. By applying the nanofiber layer 3 to the skin, the skin can be protected from external stimuli and foreign substances.

[0015] In this specification, the term "user" refers to the person to whose skin the nanofiber layer is to be attached, and the term "caregiver" refers to a person who performs at least some of the following tasks on behalf of the user: applying the formulation, transferring the nanofiber layer, and tapping (described later).

[0016] As shown in FIG. 1, the base layer 2 has a nanofiber layer arrangement portion 21 that is generally rectangular in plan view, and a pair of knob portions 22 that are connected to the nanofiber layer arrangement portion 21 and are arranged opposite each other with the nanofiber layer arrangement portion 21 in between. In the nanofiber layer arrangement portion 21, the nanofiber layer 3 is arranged in a laminated manner in the central region, and no nanofiber layer 3 is arranged in the peripheral region. The nanofiber layer 3 is not disposed on the grip portion 22.

[0017] In the nanofiber sheet 1, the base layer 2 may be colored to have a color different from that of the nanofiber layer 3. By making the base layer 2 and the nanofiber layer 3 different colors in the nanofiber sheet 1, the user or caregiver can visually and intuitively grasp the presence and position of the nanofiber layer 3 in the nanofiber sheet 1. This facilitates alignment of the target attachment area with the nanofiber layer 3 during transfer. Furthermore, by observing the lamination surface 2a of the base layer 2 after transfer, it is possible to visually determine whether the nanofiber layer 3 remains on the base layer 2 and whether the transfer was successful, and to determine whether the nanofiber layer 3 is sufficiently attached to the target attachment area. The nanofiber layer 3 formed on the base layer 2 is typically white. The base layer 2 may be colored in a color other than white, such as blue, which gives a sense of cleanliness to a user or caregiver, so that the presence and position of the nanofiber layer 3 can be visually confirmed.

[0018] <Examples of using nanofiber sheets> In a preferred use of the nanofiber sheet 1, a formulation application step and a nanofiber layer transfer step are carried out.

[0019] [Formulation application process] The formulation application step is a step of applying the formulation to the skin. In the formulation application step, the user or a caregiver applies the formulation mainly to the target area. The formulation can be applied to the skin before or after the transfer of the nanofiber layer 3. The formulation is typically applied to the skin before the transfer of the nanofiber layer in order to improve adhesion between the nanofiber layer and the skin. In the following explanation, an example in which the formulation is applied before the transfer of the nanofiber layer to the skin is given. The formulation has a different composition from the composition for forming the nanofiber layer, and preferably does not contain the first polymer of the present invention.

[0020] Preferable examples of the preparation include those having functions such as moisturizing, anti-inflammatory, sterilizing and disinfecting, and external hemorrhoidal medication. The preparation can be appropriately selected depending on the skin condition. The formulation may be applied to the skin in the form of a liquid, cream, foam or mist for ease of application to the skin. Specific examples of formulations are described below.

[0021] Applying a preparation to the skin refers to a state in which the preparation is attached, spread, carried or fixed to a target site on the skin. The means for applying the preparation to the skin is not particularly limited. For example, the preparation may be spread using a tool such as fingers or a brush, or may be sprayed using a spray or the like.

[0022] [Nanofiber layer transfer process] After the formulation application step, the user or caregiver places the nanofiber sheet 1 on the skin to which the formulation has been applied so that the nanofiber layer 3 is in direct contact with the skin, and taps the nanofiber sheet 1 with a fingertip or the like to transfer the nanofiber layer 3 to the skin. Next, the user or caregiver pinches the gripping portion 22 to peel off the base layer 2. Thereafter, the user or caregiver taps the skin with a fingertip or the like to blend the formulation with the nanofiber layer 3. This forms a nanofiber layer on the skin.

[0023] [Formulation example] The formulation preferably contains one or more selected from water, polyols, and oils that are liquid at 20°C.

[0024] Preparations containing water include, for example, aqueous liquids such as water, aqueous solutions, and aqueous dispersions. Other examples of preparations containing water include lotions, emulsions such as O / W emulsions and W / O emulsions, compositions and cosmetic creams having a lamellar structure, and aqueous liquids thickened with a thickener. From the viewpoints of moisturizing properties, improving the compatibility of the nanofiber layer attached to the skin, and excellent transferability, compositions having a lamellar structure are preferred.

[0025] Here, "good compatibility" refers to a state in which the user feels that the nanofiber layer is firmly attached to the skin (target area), and when the user touches the skin with the nanofiber layer attached with the pads of their fingers or the palm of their hand, the nanofiber layer feels as if it is evenly attached to the skin over the entire area of ​​the body that is being touched (the pads of their fingers or the palm of their hand).

[0026] When the formulation contains a polyol, examples of the polyol include alkylene glycols such as ethylene glycol, propylene glycol, 1,3-propanediol, and 1,3-butanediol; polyalkylene glycols such as diethylene glycol, dipropylene glycol, polyethylene glycol, and polypropylene glycol; and glycerins such as glycerin, diglycerin, and triglycerin. From the viewpoints of improving the compatibility of the nanofiber layer adhered to the skin and of excellent transferability, polyols that are liquid at 20°C are preferred.

[0027] When the formulation contains a polyol, the content of the polyol in the formulation is preferably 3% by mass or more, more preferably 5% by mass or more, and even more preferably 10% by mass or more from the viewpoints of improving the compatibility of the nanofiber layer adhered to the skin and excellent transferability, and from the same viewpoints, is 40% by mass or less, preferably 30% by mass or less, and more preferably 20% by mass or less. The content of the polyol in the formulation is preferably 3% by mass or more and 40% by mass or less, more preferably 5% by mass or more and 30% by mass or less, and even more preferably 10% by mass or more and 20% by mass or less.

[0028] When the formulation contains an oil that is liquid at 20°C (hereinafter, this oil will also be referred to as "liquid oil"), examples of the oil that is liquid at 20°C include linear or branched hydrocarbon oils, ester oils, higher alcohols of branched or unsaturated fatty acids, and silicone oils.

[0029] Examples of the hydrocarbon oil include liquid paraffin, squalane, squalene, n-octane, n-heptane, cyclohexane, light isoparaffin, and liquid isoparaffin, with liquid paraffin and squalane being preferred from the viewpoint of usability.

[0030] Furthermore, polar oils that are liquid at 20° C. can also be preferably used as the liquid oil, examples of which include ester oils, higher alcohols of branched or unsaturated fatty acids, silicone oils, etc. These liquid oils can be used alone or in combination of two or more.

[0031] Examples of the ester oil include esters of linear or branched fatty acids and linear or branched alcohols or polyhydric alcohols. Specific examples include isopropyl myristate, cetyl octanoate, octyldodecyl myristate, isopropyl palmitate, butyl stearate, hexyl laurate, myristyl myristate, decyl oleate, hexyldecyl dimethyloctanoate, cetyl lactate, myristyl lactate, lanolin acetate, isocetyl stearate, isocetyl isostearate, cholesteryl 12-hydroxystearate, ethylene glycol di-2-ethylhexanoate, dipentaerythritol fatty acid esters, and monoisostearate N. -Alkyl glycol, neopentyl glycol dicaprate, diisostearyl malate, glycerin di-2-heptylundecanoate, trimethylolpropane tri-2-ethylhexanoate, trimethylolpropane triisostearate, pentaerythrityl tetra-2-ethylhexanoate, glyceryl tri-2-ethylhexanoate, trimethylolpropane triisostearate, cetyl 2-ethylhexanoate, 2-ethylhexyl palmitate, diethylhexyl naphthalenedicarboxylate, benzoic acid (carbon number 12 or more) 15) Alkyl, Cetearyl Isononanoate, Tri(Caprylic / Capric) Glycerin, (Dicaprylic / Capric) Butylene Glycol, Glyceryl Trilaurate, Glyceryl Trimyristate, Glyceryl Tripalmitate, Glyceryl Triisostearate, Glyceryl Tri-2-heptylundecanoate, Glyceryl Tribehenate, Glyceryl Tri-2-heptylundecanoate, Glyceryl Triisostearate, Glyceryl Cocoate, Castor Oil Fatty Acid Methyl Ester, Oleyl Oleate, Palm Examples of suitable alkyl acrylates include 2-heptylundecyl mitate, diisobutyl adipate, 2-octyldodecyl N-lauroyl-L-glutamate, di-2-heptylundecyl adipate, ethyl laurate, di-2-ethylhexyl sebacate, 2-hexyldecyl myristate, 2-hexyldecyl palmitate, 2-hexyldecyl adipate, diisopropyl sebacate, di-2-ethylhexyl succinate, triethyl citrate, 2-ethylhexyl paramethoxycinnamate, and tripropylene glycol dipivalate. The liquid oil may also include a vegetable oil or animal oil containing an ester oil. For example, examples of liquid oils containing an ester oil include vegetable oils such as jojoba oil, olive oil, macadamia nut oil, medfoam oil, castor oil, safflower oil, sunflower oil, avocado oil, canola oil, apricot kernel oil, rice germ oil, and rice bran oil, and animal oils such as liquid lanolin.

[0032] Examples of higher alcohols include liquid higher alcohols having 12 to 20 carbon atoms, and specific examples include isostearyl alcohol and oleyl alcohol.

[0033] Examples of silicone oils include dimethylpolysiloxane, dimethylcyclopolysiloxane, methylphenylpolysiloxane, methylhydrogenpolysiloxane, and higher alcohol-modified organopolysiloxane.

[0034] When the formulation contains liquid oil, the content of the liquid oil in the formulation is preferably 1% by mass or more, more preferably 1.5% by mass or more, and even more preferably 2% by mass from the viewpoints of improving the compatibility of the nanofiber layer attached to the skin and of excellent transferability, and from the same viewpoints, is 10% by mass or less, preferably 6% by mass or less, and more preferably 4% by mass or less. The content of the liquid oil in the formulation is preferably 1% by mass or more and 10% by mass or less, more preferably 1.5% by mass or more and 6% by mass or less, and even more preferably 2% by mass or more and 4% by mass or less.

[0035] The formulation may also contain solid fats, and preferably contains pseudoceramides from the viewpoints of improving the compatibility of the nanofiber layer attached to the skin and of excellent transferability. The pseudoceramides of the present invention include those also called natural (animal) ceramides, human ceramides, and synthetic ceramides. For example, the pseudoceramides are listed as cetyl PG hydroxyethyl palmitamide in cosmetics ingredients and as N-(hexadecyloxyhydroxypropyl)-N-hydroxyethylhexadecanamide or hexadecyloxy PG hydroxyethylhexadecanamide (abbreviated name) in quasi-drugs.

[0036] <Details of the nanofiber layer> The nanofiber layer 3 is composed of nanofibers. The nanofiber layer 3 is preferably composed only of nanofibers. However, the nanofiber layer may contain other components in addition to nanofibers. The thickness of nanofibers, expressed as a circle-equivalent diameter, is generally 10 to 3000 nm, particularly 10 to 1000 nm. The thickness of nanofibers can be measured, for example, by observation with a scanning electron microscope (SEM).

[0037] The inventors focused on the moisture absorption of the polymer used in the nanofiber layer 3 in a high-temperature, high-humidity environment and discovered that by blending the nanofiber layer 3 with a first polymer that has a relatively low moisture absorption in a high-temperature, high-humidity environment and a second polymer that has a relatively high moisture absorption, it is possible to obtain a nanofiber sheet with improved transferability and conformability. This will be explained in detail below.

[0038] In the nanofiber sheet 1 of the present invention, the nanofiber layer 3 comprises a first polymer having a moisture absorption rate of 1% or less in a hot and humid environment, and a second polymer having a moisture absorption rate of more than 1% and 40% or less in a hot and humid environment. The first polymer is the part that becomes the core of the nanofiber layer 3 . The second polymer contributes to modifying the surface of the fiber.

[0039] The nanofiber layer 3 is formed, for example, by electrospinning, by depositing nanofibers on the base layer 2 using a nanofiber layer-forming composition (described below), which is a mixed liquid of a first polymer, a second polymer, and a solvent. During the formation of this nanofiber layer 3, the solvent in the nanofiber layer-forming composition volatilizes, and the nanofiber layer 3 made of the first polymer and the second polymer is formed. The composition for forming a nanofiber layer and the method for producing a nanofiber sheet will be described later.

[0040] [Method for measuring moisture absorption of polymers in a high-temperature, high-humidity environment] In this specification, the moisture absorption of a polymer in a high-temperature and high-humidity environment is measured by the measurement method described below. 1 g of the polymer to be measured is left standing in an incubator at 40°C and 90% RH (high temperature and humidity environment) for 24 hours, and the polymer to be measured is subjected to a high temperature and humidity load. The weight of the polymer to be measured before the high temperature and humidity load is measured immediately after leaving it to stand in an environment of 25°C and 50% RH for 1 minute is defined as the "initial weight," and the weight of the polymer to be measured after the high temperature and humidity load is measured immediately after leaving it to stand in an environment of 25°C and 50% RH for 1 minute immediately after taking it out of the incubator is defined as the "weight after high temperature and humidity load." The moisture absorption of the polymer to be measured is calculated using the following formula (1). Moisture absorption = (weight after high temperature and humidity load - initial weight) / initial weight × 100 (%) ... (1) In this specification, unless otherwise specified, "moisture absorption" means "moisture absorption in a high-temperature and high-humidity environment."

[0041] [First polymer] The first polymer has a moisture absorption of 1% or less, preferably 0.9% or less, from the viewpoint of forming a nanofiber layer that is less susceptible to the use environment, has excellent transferability, and is easy to maintain good quality. From the same viewpoint, the moisture absorption is preferably 0.1% or more, more preferably 0.6% or more.

[0042] In addition to the moisture absorption mentioned above, the physical properties of the first polymer can also be explained from the viewpoint of water insolubility. Specifically, the first polymer is preferably a polymer that, when 1 g of the polymer is weighed and immersed in 10 g of deionized water under an environment of 1 atmosphere and 23°C, does not dissolve more than 0.5 g of the immersed polymer after 24 hours.

[0043] More specifically, from the viewpoint of obtaining a nanofiber layer that has excellent transferability and is easy to maintain good quality, it is more preferable to use one or more polymers selected from polyvinyl butyral resin, polyurethane resin, and polylactic acid as the first polymer, and it is even more preferable to use polyvinyl butyral resin.

[0044] [Second polymer] From the viewpoints of good compatibility, excellent transferability, and reducing the occurrence of twisting or air bubbles in the nanofiber layer adhered to the skin, the second polymer has a moisture absorption of more than 1%, preferably 3% or more, more preferably 5% or more, and even more preferably 8% or more, and from the same viewpoints, 40% or less, preferably 32% or less, more preferably 29% or less, and even more preferably 18% or less. The moisture absorption of the second polymer is more than 1% and 40% or less, preferably 3% or more and 32% or less, more preferably 5% or more and 29% or less, and even more preferably 8% or more and 18% or less.

[0045] The second polymer may contain one or more polymers selected from polyvinylpyrrolidone, polyvinylpyrrolidone copolymers, polyalkylene glycols, and silicone structure-containing copolymers. From the viewpoint of improving the compatibility of the nanofiber layer adhered to the skin and from the viewpoint of excellent transferability, it is preferable to use one or more polymers selected from polyvinylpyrrolidone copolymers and polyalkylene glycols.

[0046] Examples of polyvinylpyrrolidone copolymers include vinyl acetate-vinylpyrrolidone copolymer, vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer-diethyl sulfate copolymer, and vinylcaprolactam-vinylpyrrolidone-dimethylaminopropyl methacrylamide-methacryloylaminopropyl lauryldimonium chloride copolymer. From the viewpoints of improving the compatibility of the nanofiber layer adhered to the skin and of excellent transferability, it is preferable to use vinyl acetate-vinylpyrrolidone copolymer. The content of one or more polymers selected from polyvinylpyrrolidone, polyvinylpyrrolidone copolymers, polyalkylene glycols, and silicone structure-containing copolymers relative to the total amount of the second polymer is preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 95% by mass or more, from the viewpoint of improving the compatibility of the nanofiber layer.

[0047] Vinyl acetate-vinylpyrrolidone copolymer is a copolymer obtained by polymerizing vinyl acetate and vinylpyrrolidone, and contains both vinyl acetate-based and vinylpyrrolidone-based structures. Here, the vinyl acetate-based structure is designated as VP, and the vinylpyrrolidone-based structure is designated as VA. From the viewpoints of achieving good compatibility of the nanofiber layer adhered to the skin and excellent transferability, the VP:VA ratio in the vinyl acetate-vinylpyrrolidone copolymer of the present invention is preferably in the range of VP:VA = 20:80 to 80:20, and more preferably in the range of VP:VA = 25:75 to 65:35. The "ratio" in this section refers to the molar ratio, and the amount of remaining monomer relative to the charged monomer composition can be calculated by gas chromatography.

[0048] More specifically, the following commercially available products can be used as the polyvinylpyrrolidone copolymer. Product name: Eiftact K30-PH (Dai-ichi Kogyo Seiyaku Co., Ltd.) Product name: PVA / VA E735 (Ashland Japan Co., Ltd.) Product name: PLASDONE (registered trademark) S630 (Ashland Japan Co., Ltd.) Product name: PVA / VA E535 (Ashland Japan Co., Ltd.) Product name: PVA / VA E335 (Ashland Japan Co., Ltd.) Product name: Gafquat (registered trademark) 734 (Ashland Japan Co., Ltd.) Product name: Aquastyle300N (Ashland Japan Co., Ltd.)

[0049] Examples of polyalkylene glycols include polyethylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene glycol. From the viewpoints of improving the compatibility of the nanofiber layer attached to the skin and of excellent transferability, it is preferable to use polyoxyethylene polyoxypropylene glycol.

[0050] The average number of moles of ethylene oxide added in polyoxyethylene polyoxypropylene glycol is preferably 5 to 200, more preferably 10 to 30, from the viewpoints of good compatibility, excellent transferability, and reducing twisting of the nanofiber layer attached to the skin and the inclusion of air bubbles. Also, from the same viewpoints, the average number of moles of propylene oxide added is preferably 5 to 100, more preferably 10 to 30. The average number of moles of ethylene oxide added can be calculated, for example, by the method described in "JIS K 0070-1992 7.1 Neutralization titration method." 1 It can be determined using H-NMR.

[0051] More specifically, the following commercially available polyethylene glycol adducts can be used: Product name: Pronon (registered trademark) 124P (NOF Corporation) Product name: Pronon (registered trademark) 237P (NOF Corporation) Product name: Pronon (registered trademark) 407P (NOF Corporation)

[0052] More specifically, the following commercially available products can be used as the silicone structure-containing copolymer. Product name: OS-88TE-E (Kao Corporation) Product name: Silicone KF-6011 (Shin-Etsu Chemical Co., Ltd.)

[0053] In addition, the following commercially available products can be used as the second polymer. Product name: Gantrez (registered trademark)-es225 (Ashland Japan Co., Ltd.)

[0054] In the nanofiber layer 3 of the nanofiber sheet 1 of the present invention, the content of the first polymer is preferably 40% by mass or more, more preferably 48% by mass or more, even more preferably 54% by mass or more, still more preferably 60% by mass or more, and even more preferably 64% by mass or more, from the viewpoints of good compatibility, excellent transferability, and reducing wrinkling and air bubble inclusion in the nanofiber layer adhered to the skin, and from the same viewpoints, it is preferably 98% by mass or less, more preferably 89% by mass or less, even more preferably 85% by mass or less, still more preferably 82% by mass or less, and even more preferably 79% by mass or less. The content of the first polymer is preferably 40% by mass or more and 98% by mass or less, more preferably 48% by mass or more and 89% by mass or less, even more preferably 54% by mass or more and 85% by mass or less, still more preferably 60% by mass or more and 82% by mass or less, and even more preferably 64% by mass or more and 79% by mass or less.

[0055] In the nanofiber layer 3 of the nanofiber sheet 1 of the present invention, the content of the second polymer is preferably 2% by mass or more, more preferably 12% by mass or more, even more preferably 15% by mass or more, still more preferably 18% by mass or more, and even more preferably 21% by mass or more, from the viewpoints of good compatibility, excellent transferability, and reducing wrinkling and air bubble inclusion in the nanofiber layer adhered to the skin. From the same viewpoints, the content of the second polymer is preferably 60% by mass or less, more preferably 52% by mass or less, even more preferably 46% by mass or less, still more preferably 40% by mass or less, and even more preferably 34% by mass or less. The content of the second polymer is preferably 2% by mass or more and 60% by mass or less, more preferably 12% by mass or more and 52% by mass or less, even more preferably 15% by mass or more and 46% by mass or less, still more preferably 18% by mass or more and 40% by mass or less, and even more preferably 21% by mass or more and 34% by mass or less.

[0056] [Mixing ratio of first polymer and second polymer] From the viewpoint of further improving both the transferability and compatibility of the nanofiber layer, it is preferable to define the blending ratio of the first polymer, which has a relatively low moisture absorption rate in a high-temperature, high-humidity environment, to the second polymer, which has a relatively high moisture absorption rate, as follows: In the nanofiber layer 3 of the nanofiber sheet 1 of the present invention, the proportion of the second polymer in the total polymer, including the first polymer and the second polymer (hereinafter sometimes simply referred to as the proportion of the second polymer), is preferably 0.05 or more, more preferably 0.11 or more, even more preferably 0.15 or more, even more preferably 0.18 or more, and even more preferably 0.21 or more, from the viewpoints of good compatibility, excellent transferability, and reducing wrinkling and air bubble inclusion in the nanofiber layer adhered to the skin; and from the same viewpoint, it is preferably 0.60 or less, more preferably 0.52 or less, even more preferably 0.46 or less, even more preferably 0.40 or less, even more preferably 0.38 or less, and even more preferably 0.34 or less. The ratio of the second polymer to the total polymer, which is the combination of the first polymer and the second polymer, is preferably 0.05 or more and 0.60 or less, more preferably 0.11 or more and 0.52 or less, even more preferably 0.15 or more and 0.46 or less, still more preferably 0.18 or more and 0.40 or less, still more preferably 0.21 or more and 0.38 or less, and still more preferably 0.21 or more and 0.34 or less. The proportion of the second polymer is calculated by the following formula (2), where the mass (content) of the first polymer in the nanofiber layer 3 is M1 and the mass (content) of the second polymer is M2. Ratio of second polymer = M2 / (M1+M2) ... (2)

[0057] In the nanofiber sheet of the present invention, the nanofiber layer is composed of a first polymer with relatively low moisture absorption and a second polymer with relatively high moisture absorption in the above-mentioned blending ratio, thereby improving the moisture resistance of the nanofiber layer 3. This prevents the nanofiber layer from dissolving due to moisture absorption and remaining on the base layer, even when the nanofiber sheet is stored or used in a hot and humid environment. This improves the transferability of the nanofiber layer 3. Furthermore, even when the skin to which the nanofiber layer 3 is attached is exposed to hot and humid conditions for a long period of time, such as in a bathroom or changing room, the nanofiber layer is resistant to dissolution, allowing the nanofiber layer 3 to maintain a stable film shape and quality. Furthermore, when the target area for attachment is a wound on the skin, the nanofiber layer 3 transferred to the skin is placed in a state where it is easy to absorb exudate, and the target area for attachment is in an environment where the humidity is high. However, by improving the moisture resistance of the nanofiber layer 3, the nanofiber layer 3 is less likely to be dissolved by exudate, and the quality of the nanofiber layer 3 can be stably maintained. Furthermore, when the target area for attachment is inside the oral cavity, such as on the teeth or gums, which is a humid environment, the nanofiber layer 3 transferred to the oral cavity is placed in an environment where it is prone to absorbing saliva. However, by improving the moisture resistance of the nanofiber layer 3, the nanofiber layer 3 is less likely to be dissolved by saliva, and the quality of the nanofiber layer 3 can be stably maintained. As described above, the nanofiber layer 3 of the nanofiber sheet 1 of the present invention has excellent moisture resistance even when placed in a high-temperature or high-humidity environment, and is therefore less susceptible to the effects of the storage environment or usage environment, maintaining a stable film shape and quality.

[0058] In addition, by including the second polymer, the adhesion of the nanofiber layer 3 to the skin can be improved, resulting in good compatibility with the skin. The nanofiber layer 3 can continuously maintain good adhesion even in high temperature or high humidity environments, resulting in a nanofiber layer 3 that is less affected by the usage environment and can continuously maintain good compatibility with the skin. Furthermore, since the nanofiber layer 3 is well adapted to the skin, it is less likely to become twisted or have air bubbles mixed in, and the boundary between the skin with the nanofiber layer 3 attached and the skin without the nanofiber layer 3 is difficult to distinguish, resulting in a natural appearance that does not make you feel the presence of the nanofiber layer 3. Furthermore, the nanofiber layer 3 of the nanofiber sheet 1 of the present invention adheres firmly to the skin, even on uneven skin surfaces such as wounds, by conforming to the unevenness of the skin, making it less likely to cause any sensory discomfort on the skin.

[0059] Furthermore, the inclusion of the second polymer improves the compatibility of the nanofiber layer 3 with the formulation, allowing the formulation to be present throughout the entire nanofiber layer 3 attached to the skin, and enabling the formulation held between the fibers to remain in good contact with the skin for a long period of time during use. As a result, the penetration of the formulation into the skin is further promoted, and the effect of the formulation on the skin can be improved. Furthermore, as described above, the nanofiber layer 3 of the nanofiber sheet 1 of the present invention has excellent moisture resistance even in high-temperature or high-humidity environments, making it less susceptible to the effects of the usage environment and more likely to maintain a stable film shape. This allows the preparation to be stably retained between the fibers for a long period of time regardless of the usage environment, further improving the effect of the preparation on the skin.

[0060] Thus, the nanofiber sheet 1 of the present invention has good skin compatibility and excellent transferability. Furthermore, the nanofiber sheet 1 is not easily affected by its storage or usage environment, and can stably maintain its excellent transferability and good compatibility, resulting in a stable quality.

[0061] Furthermore, when the nanofiber sheet 1 is wrapped in a packaging material to form a package, the range of options for the materials used for the packaging material and the packaging form can be expanded. For example, even if the packaging material is made of a material with low moisture resistance, the nanofiber sheet 1 has excellent moisture resistance and is therefore less susceptible to the storage environment, allowing the quality of the nanofiber sheet to be stably maintained. For example, from the standpoint of hygiene and the like, it is typically preferable for nanofiber sheets to be individually packaged, but multiple nanofiber sheets may be contained in a single packaging material to form a package. When multiple nanofiber sheets are contained in a package, they are typically taken out one by one for use, and the remaining nanofiber sheets are stored within the package. Even in this type of use, the nanofiber sheet 1 has excellent moisture resistance, so the quality of the nanofiber sheets stored within the package can be maintained. Furthermore, when the nanofiber sheet 1 is packaged in packaging material, even if moisture from the atmosphere gets into the package, the nanofiber sheet 1 has excellent moisture resistance as described above, so the package can maintain stable quality.

[0062] <Details of the base layer> The base layer 2 holds the nanofiber layer 3 on the lamination surface 2a. To improve the peelability of the base layer from the nanofiber layer during transfer, the base layer 2 is preferably a fiber aggregate composed of fibers. By using a fiber aggregate, the base layer has breathability and reduces the number of contact points between the nanofiber layer and the base layer 2, improving peelability. The substrate layer 2 may be a nonwoven fabric, a woven fabric, or a knitted fabric, and is typically made of a nonwoven fabric.

[0063] Furthermore, it is preferable that the base layer 2 is made of a highly hygroscopic material having an official moisture regain of 8% or more. In addition to blending the first polymer and the second polymer in the above ratio to form a nanofiber layer with excellent moisture resistance, by forming the base layer 2 using highly hygroscopic fibers, it is possible to obtain a nanofiber sheet 1 with even better moisture resistance. That is, by forming the base layer 2 from a highly hygroscopic material, even in a high-temperature and high-humidity storage or usage environment, the base layer 2 is likely to absorb excessive moisture, which further reduces the occurrence of an event where the nanofiber layer 3 dissolves and remains on the base layer 2 during transfer. As a result, excellent transferability and good compatibility can be stably maintained. By constructing a nanofiber sheet using such a highly hygroscopic substrate layer, it is possible to provide users with a nanofiber sheet of stable quality that is less affected by the storage environment or usage environment, has excellent transferability, and is comfortable against the skin. Rayon-based fibers can be used for the base layer 2 having an official moisture regain of 8% or more. Examples of rayon-based fibers that can be used include rayon and mixtures of rayon with polyethylene terephthalate, polyethylene, and polypropylene. The official moisture regain is measured in a testing room or device at a temperature of 20°C and 65% RH according to the method described in JIS L0105:2020.

[0064] For the base material layer 2, it is particularly preferable to use a material that is highly hygroscopic and, as will be described later, is difficult to charge, and rayon is a suitable example.

[0065] [Initial withstand voltage of base layer] From the viewpoint of stabilizing the quality of the nanofiber sheet by making it difficult for the nanofiber layer to float from the base layer, it is preferable that the initial withstand voltage of the base layer 2 be 0.3 kV or less. Such a low-charge base layer with a low initial withstand voltage is less likely to become charged, and the electrostatic repulsion between the base layer and the nanofiber layer can be kept low, making it difficult for the nanofiber layer to float from the base layer and stabilizing the quality of the nanofiber sheet. Furthermore, when a nanofiber layer is formed on a low-charge base layer by electrospinning in a conventional manner, the nanofibers are less likely to be electrically repelled by the base layer, allowing the nanofibers to be deposited accurately at desired positions on the base layer. The nanofiber sheet of the present invention is used by transferring the nanofiber layer and peeling off the base layer as described above. Therefore, it is preferable that no adhesive layer, such as an adhesive, is provided between the nanofiber layer and the base layer. To improve the peelability of the base layer from the nanofiber layer, the laminated surface of the base layer may be subjected to a peeling treatment such as coating with a silicone resin or corona discharge treatment, if necessary.

[0066] (Method for measuring initial withstand voltage) The initial withstand voltage of the base layer is measured in an environment of 23°C and 50% RH using an Honest Meter (Shishido Electrostatic Corporation, model number H-0110) in accordance with the half-life measurement method specified in the electrostatic charge test method of JIS L1094: 2014. The initial withstand voltage is measured on the laminated surface of the nanofiber layer in the base layer. The measurement conditions were as follows: applied voltage: 10 kV, distance between the application electrode and the sample: 15 mm, distance between the voltage receiving part and the sample: 15 mm.

[0067] <Other configurations>

[0068] [Moisture absorption of nanofiber layer] From the viewpoint of improving moisture resistance, transferability, and compatibility of the nanofiber layer, the moisture absorption of the nanofiber layer is preferably 1% to 10%, more preferably 2% to 9%, and even more preferably 3% to 7%. The moisture absorption of the nanofiber layer in each example described below is shown in Tables 1 to 4. The moisture absorption of the nanofiber layer is calculated as a weighted average according to the following formula (3). In formula (3), M1 is the mass (content) of the first polymer in the nanofiber layer 3, M2 is the mass (content) of the second polymer in the nanofiber layer 3, A1 is the moisture absorption of the first polymer, and A2 is the moisture absorption of the second polymer. The moisture absorption is calculated using formula (1) above. Moisture absorption of nanofiber layer = (A1 × M1 + A2 × M2) / (M1 + M2) ... (3)

[0069] [Relationship between moisture absorption of the first polymer and the second polymer] From the viewpoint of improving the moisture resistance, transferability and compatibility of the nanofiber layer, the difference in moisture absorption between the first polymer and the second polymer is preferably 5% to 30%, more preferably 7% to 16%.

[0070] <Skin protection kit> As shown in Figure 2, the skin protection kit 10 of the present invention comprises a package 5 containing the nanofiber sheet 1, and a container 6 filled with a formulation. While five packages 5 are shown in Figure 2, the number of packages 5 is not limited and may be one or more. Furthermore, the packages 5 are typically individual packages containing one nanofiber sheet 1, but one package 5 may contain multiple nanofiber sheets 1.

[0071] The package 5 is constructed by accommodating the nanofiber sheet 1 in, for example, a bag-shaped packaging material 4. The packaging material 4 can be made of a known material. The package 5 may be aluminum packaging. Because aluminum packaging has low moisture permeability, it is possible to provide a nanofiber sheet 1 with even more stable quality. However, the moisture resistance of the aluminum packaging is also affected by the tightness of the seal that makes up the aluminum packaging, so there are cases where the aluminum packaging cannot completely prevent moisture. Even in such cases, by using the nanofiber sheet 1 of the present invention, which has excellent moisture resistance, the quality of the nanofiber sheet 1 in the package 5 can be maintained stably and well, even when the package 5 is stored in a high-temperature, high-humidity environment. Furthermore, even if moisture such as humidity gets into the packaging body 5 during the aluminum packaging process during the manufacturing process of the packaging body, the nanofiber sheet 1 has excellent moisture resistance, so the quality of the nanofiber layer 3 can be stably and well maintained.

[0072] <Method of manufacturing nanofiber sheet> The nanofiber sheet 1 is produced by depositing nanofibers on the lamination surface 2a of the base layer 2 by, for example, electrospinning to form the nanofiber layer 3.

[0073] [Device configuration] FIG. 3 is a schematic diagram of an electrospinning apparatus 30 (hereinafter referred to as apparatus 30) for carrying out the electrospinning method. As shown in FIG. 3, the apparatus 30 includes a syringe 31, a high voltage source 32, a conductive collector 33, and a syringe pump . Syringe 31 includes cylinder 31a, piston 31b, and capillary 31c. Capillary 31c has an inner diameter of approximately 10 to 1000 μm. Cylinder 31a is filled with a solution of a polymer compound that is a raw material for nanofibers. The polymer compound solution is a composition (mixture) for forming a nanofiber layer that contains a first polymer and a second polymer as polymer compounds, and a solvent. High voltage source 32 is, for example, a DC voltage source of 10 to 30 kV. The positive electrode of high voltage source 32 is electrically connected to the nanofiber layer forming composition in syringe 31. The negative electrode of high voltage source 32 is grounded. The conductive collector 33 is, for example, a flat metal plate that is grounded. The substrate layer 2 on which the nanofiber layer is to be formed is placed on the conductive collector 33. The syringe pump 34 controls the discharge of the nanofiber layer forming composition from the syringe 31 so that a desired amount of the nanofiber layer forming composition is discharged from the capillary 31c. The distance between the tip of the capillary 31c of the syringe 31 and the conductive collector 33 is set to, for example, about 30 to 300 mm. The device 30 can be operated in the atmosphere. There are no restrictions on the operating environment, and the temperature can be 20 to 40°C and the humidity can be 10 to 50% RH.

[0074] [Method of manufacturing nanofiber sheets using the device] A method for producing the above-mentioned nanofiber sheet 1 using the apparatus 30 will now be described. First, the substrate layer 2 is placed on the conductive collector 33 . Next, with a voltage applied between the syringe 31 and the conductive collector 33, the piston 31b of the syringe 31 is gradually pushed in, and the nanofiber layer forming composition is extruded from the tip of the capillary 31c. In the extruded nanofiber layer forming composition, the solvent evaporates and the polymer compound (the solute) solidifies, and the nanofibers are stretched and deformed by the potential difference between the conductive collector 33 and the base layer 2, forming nanofibers that are attracted to the conductive collector 33. As a result, nanofibers are deposited on the lamination surface 2a of the base layer 2 placed on the conductive collector 33, and a nanofiber sheet 1 is produced in which a nanofiber layer 3 is formed on the base layer 2.

[0075] [Nanofiber layer forming composition] The nanofiber layer forming composition is a mixed liquid of a first polymer, a second polymer, and a solvent.

[0076] The solvent contains one or more selected from monohydric alcohols and ketones. Monohydric alcohols and ketones are volatile substances. From the viewpoint of improving the compatibility of the formed nanofiber layer, the solvent preferably contains one or more monohydric alcohols selected from ethanol, isopropyl alcohol, and butyl alcohol, more preferably ethanol. From the same viewpoint, the solvent preferably contains acetone as a ketone. The type of solvent used can be determined appropriately depending on the type of first polymer, and a solubilizer for the first polymer can be used as the solvent. For example, when polyvinyl butyral resin or polyurethane resin is used as the first polymer, ethanol can be used as the solvent. When polylactic acid is used as the first polymer, acetone can be used as the solvent. The solvent may also contain water. When forming a nanofiber layer using electrospinning, the solvent is preferably a volatile substance, since the nanofibers are formed by volatilizing the solvent. The vapor pressure of the volatile substance at 20°C is preferably 0.01 kPa or more and 106.66 kPa or less, more preferably 0.13 kPa or more and 66.66 kPa or less, even more preferably 0.67 kPa or more and 40.00 kPa or less, and even more preferably 1.33 kPa or more and 40.00 kPa or less.

[0077] In the present invention, the nanofiber layer-forming composition is preferably formulated so that the value of M2 / (M1+M2) is 0.05 to 0.60, where M1 is the mass of the first polymer and M2 is the mass of the second polymer in the nanofiber layer-forming composition. In this case, the solvent is preferably mixed in a proportion of 50 to 100% by mass, more preferably 80 to 95% by mass, of the nanofiber layer-forming composition. In addition, the ratio of the second polymer to the total polymer, which is the sum of the first polymer and the second polymer, in the nanofiber layer 3 formed using the above-mentioned nanofiber layer-forming composition (ratio of the second polymer) is preferably 0.05 or more and 0.60 or less. Furthermore, since the nanofiber layer 3 has excellent moisture resistance, even if the manufacturing environment (temperature, humidity, etc.) during manufacturing of the nanofiber sheet 1 using the device 30 changes significantly, a nanofiber sheet 1 of good quality can be manufactured stably.

[0078] Although the present invention has been described above based on the preferred embodiments, the present invention is not limited to the above embodiments.

[0079] The present invention can also be configured as follows. <1> A nanofiber sheet comprising a base layer and a nanofiber layer disposed on one surface of the base layer, wherein the base layer is peeled off during use, and the nanofiber layer is attached to a target site, The nanofiber layer comprises: a first polymer having a moisture absorption rate of 1% or less when left standing in a high temperature and humidity environment (40°C, 90% RH for 24 hours); The second polymer has a moisture absorption rate of more than 1% and less than 40% in a high temperature and humidity environment (left standing for 24 hours at 40°C and 90% RH). Contains Nanofiber sheet. <2> When the mass of the first polymer in the nanofiber layer is M1 and the mass of the second polymer is M2, the value of M2 / (M1+M2) is 0.05 or more and 0.60 or less. The aforementioned <1> The nanofiber sheet according to claim 1. <3> The moisture absorption of the first polymer is preferably 0.9% or less, preferably 0.1% or more, more preferably 0.6% or more. The aforementioned <1> or <2> The nanofiber sheet according to claim 1. <4> As the first polymer, it is preferable to use one or more polymers selected from polyvinyl butyral resin, polyurethane resin, and polylactic acid, and it is more preferable to use polyvinyl butyral resin. <1> from <3> 10. The nanofiber sheet according to any one of the preceding items. <5> The content of the first polymer in the nanofiber layer in the nanofiber sheet is preferably 40% by mass or more, more preferably 48% by mass or more, even more preferably 54% by mass or more, still more preferably 60% by mass or more, still more preferably 64% by mass or more, and is preferably 98% by mass or less, more preferably 88% by mass or less, even more preferably 85% by mass or less, still more preferably 80% by mass or less, and still more preferably 78% by mass or less. The aforementioned <1> ~ <4> 10. The nanofiber sheet according to any one of the preceding items. <6> The moisture absorption of the second polymer is preferably 3% or more, more preferably 5% or more, even more preferably 8% or more, and is preferably 32% or less, more preferably 29% or less, even more preferably 18% or less. The aforementioned <1> ~ <5> 10. The nanofiber sheet according to any one of the preceding items. <7> The second polymer preferably contains one or more polymers selected from polyvinylpyrrolidone, polyvinylpyrrolidone copolymers, polyalkylene glycols, and silicone structure-containing copolymers, and more preferably contains one or more polymers selected from polyvinylpyrrolidone copolymers and polyalkylene glycols. The aforementioned <1> ~ <6> 10. The nanofiber sheet according to any one of the preceding items. <8> The second polymer is preferably one or more selected from the group consisting of copolymers of polyvinylpyrrolidone, such as vinyl acetate-vinylpyrrolidone copolymer, vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer, diethyl sulfate, and vinylcaprolactam-vinylpyrrolidone-dimethylaminopropyl methacrylamide-methacryloylaminopropyl lauryldimonium chloride, and more preferably vinyl acetate-vinylpyrrolidone copolymer. The aforementioned <7> The nanofiber sheet according to claim 1. <9> When the vinyl acetate-vinylpyrrolidone copolymer is used as the second polymer and the structure of the vinyl acetate-vinylpyrrolidone copolymer based on vinyl acetate is VP and the structure of the vinyl acetate-vinylpyrrolidone copolymer based on vinylpyrrolidone is VA, the ratio of VP to VA (VP:VA) is preferably in the range of VP:VA=20:80 to 80:20, more preferably in the range of VP:VA=25:75 to 65:35. The aforementioned <8> The nanofiber sheet according to claim 1. <10> The second polymer preferably contains one or more polyalkylene glycols selected from polyethylene glycol, dipropylene glycol, tripropylene glycol, polypropylene glycol, and polyoxyethylene polyoxypropylene glycol, and more preferably contains polyoxyethylene polyoxypropylene glycol. The aforementioned <7> The nanofiber sheet according to claim 1. <11> The second polymer is made of the polyoxyethylene polyoxypropylene glycol, and the average number of moles of ethylene oxide added to the polyoxyethylene polyoxypropylene glycol is preferably 5 to 200, more preferably 10 to 30, and the average number of moles of propylene oxide added is preferably 5 to 100, more preferably 10 to 30. The aforementioned <10> The nanofiber sheet according to claim 1. <12> The content of the second polymer in the nanofiber layer in the nanofiber sheet is preferably 2% by mass or more, more preferably 12% by mass or more, even more preferably 15% by mass or more, still more preferably 18% by mass or more, still more preferably 21% by mass or more, and is preferably 60% by mass or less, more preferably 52% by mass or less, even more preferably 48% by mass or less, still more preferably 40% by mass or less, and still more preferably 34% by mass or less. The aforementioned <1> from <11> 10. The nanofiber sheet according to any one of the preceding items. <13> the ratio of the content of the second polymer to the total polymer content, which is the sum of the content of the first polymer and the content of the second polymer, in the nanofiber layer of the nanofiber sheet is preferably 0.11 or more, more preferably 0.15 or more, even more preferably 0.18 or more, still more preferably 0.21 or more, and is preferably 0.52 or less, more preferably 0.46 or less, even more preferably 0.40 or less, and still more preferably 0.38 or less; The aforementioned <1> from <12> 10. The nanofiber sheet according to any one of the preceding items. <14> The official moisture regain of the base layer, as determined by the method described in JIS L0105:2020, is 8% or more. The aforementioned <1> from <13> 10. The nanofiber sheet according to any one of the preceding items. <15> The substrate layer is made of rayon with an official moisture regain of 8% or more. The aforementioned <14> The nanofiber sheet according to claim 1. <16> The initial withstand voltage of the base material layer, determined by the half-life measurement method specified in the electrostatic charge test method of JIS L1094:2014 under an environment of 23°C and 50% RH, is 0.3 kV or less. The aforementioned <1> from <15> 10. The nanofiber sheet according to any one of the preceding items. <17> The moisture absorption of the nanofiber layer is preferably 1% or more and 10% or less, more preferably 2% or more and 9% or less, and even more preferably 3% or more and 7% or less. <1> ~ <16> 10. The nanofiber sheet according to any one of the preceding items. <18> The difference in moisture absorption between the first polymer and the second polymer of the nanofiber layer is preferably 5% or more and 30% or less, more preferably 7% or more and 16% or less. The aforementioned <1> from <17> 10. The nanofiber sheet according to any one of the preceding items. <19> The nanofiber sheet is for skin protection. The aforementioned <1> from <18> 10. The nanofiber sheet according to any one of the preceding items. <20> a formulation containing one or more selected from water, polyols, and oils that are liquid at 20°C; The aforementioned <1> from <19> The nanofiber sheet according to any one of A kit comprising: <21> A nanofiber sheet comprising a base layer and a nanofiber layer disposed on one surface of the base layer, wherein the base layer is peeled off during use, and the nanofiber layer is attached to a target site, The nanofiber layer comprises: a first polymer having a moisture absorption rate of 1% or less when left standing in a high temperature and humidity environment (40°C, 90% RH for 24 hours); The second polymer has a moisture absorption rate of 5% to 29% in a high-temperature, high-humidity environment (40°C, 90% RH for 24 hours). Including, When the mass of the first polymer in the nanofiber layer is M1 and the mass of the second polymer is M2, the value of M2 / (M1+M2) is 0.05 or more and 0.60 or less. Nanofiber sheet. <22> A method for producing a nanofiber sheet comprising: a base layer; and a nanofiber layer disposed on one surface of the base layer; wherein the base layer is peeled off during use, and the nanofiber layer is attached to a target site; The method for producing a nanofiber sheet includes a step of applying a nanofiber layer-forming composition to one surface of the base layer by electrospinning to form the nanofiber layer; The nanofiber layer forming composition is a first polymer having a moisture absorption rate of 1% or less when left standing in a high temperature and high humidity environment (40°C, 90% RH for 24 hours); a second polymer whose moisture absorption rate in a high temperature and humidity environment (left to stand for 24 hours at 40°C and 90% RH) is more than 1% and not more than 40%; Alcohol and Contains A method for manufacturing nanofiber sheets. <23> When the mass of the first polymer in the nanofiber layer forming composition is M1 and the mass of the second polymer is M2, the value of M2 / (M1+M2) is 0.05 or more and 0.60 or less. The aforementioned <22> A method for producing the nanofiber sheet described above.

[0080] <Example> The present invention will be further described below with reference to examples, but the scope of the present invention is not limited to such examples.

[0081] <<Test Example 1: Examination of the blending ratio of the first polymer and the second polymer>> In Examples 1 to 12, nanofiber sheets were produced using compositions for forming nanofiber layers in which the mass ratio (blending ratio) of the first polymer to the second polymer was varied, and the usability of the nanofiber sheets was evaluated before and after high temperature and humidity conditions. In addition, the moisture resistance of cast films (also called polymer coatings) formed using the first polymer and the second polymer blended at the mass ratios of each example and comparative example was evaluated. Although the fibers of the cast films subjected to the moisture resistance evaluation were not nanofiber-shaped, it was confirmed that moisture resistance evaluation results equivalent to those obtained when nanofibers were used were obtained.

[0082] [Preparation of nanofiber layer-forming composition] As a nanofiber layer forming composition for forming the nanofiber layer of the nanofiber sheets of Examples 1 to 12, a mixture of the following first polymer, second polymer, and solvent was prepared. (First polymer) A polyvinyl butyral resin (product name: S-LEC (registered trademark) BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated by the above formula (1) was 0.9%. (Second polymer) The second polymer used was a vinyl acetate-vinylpyrrolidone copolymer (product name: PLASDONE® S630, Ashland Japan Co., Ltd.). The moisture absorption of this polymer calculated using the above formula (1) was 16.8%. (solvent) As a solvent, 99% synthetic alcohol (Nippon Synthetic Alcohol Co., Ltd.), which is an absolute alcohol with an ethanol content of 99.5% by volume or more, was used. In the following description of the examples, this absolute alcohol will be referred to as "ethanol." Note that ethanol easily absorbs moisture from the air, and the ethanol content will not be 100% by volume. Therefore, when the 99% synthetic alcohol is used as a solvent, the solvent will contain moisture. Ethanol was mixed in a proportion of 93 mass % in the composition.

[0083] In each of Examples 1 to 12, the mass ratio of the first polymer to the second polymer (first polymer:second polymer) in the composition for forming a nanofiber layer was as follows. (Example 1) 71.4:28.6 (Example 2) 95.2:4.8 (Example 3) 90.9:9.1 (Example 4) 87.0:13.0 (Example 5) 83.3:16.7 (Example 6) 76.9:23.1 (Example 7) 66.7:33.3 (Example 8) 62.5:37.5 (Example 9) 55.6:44.4 (Example 10) 50.0:50.0 (Example 11) 45.5:54.5 (Example 12) 41.7:58.3

[0084] [Manufacturing nanofiber sheets] A rayon nonwoven fabric (product name: Omikenshi 45, Omikenshi Co., Ltd.) was used as the substrate layer, and a nanofiber layer was formed on the substrate layer using the above-mentioned nanofiber layer-forming composition by electrospinning using the above-mentioned device 30, to produce the nanofiber sheets of each example. The conditions for producing the nanofiber sheet are as follows. Applied voltage: 27 kV, distance between capillary collectors: 185 mm, discharge rate of nanofiber layer forming composition: 1 ml / h, production environment: 28°C, 36% RH. The nanofiber layer thus obtained in each example had a thickness of 30 μm and the nanofibers had a thickness of 300 to 600 nm. The content (mass%) of the first polymer and the second polymer in the nanofiber layer of the nanofiber sheet of each Example produced, and the proportion of the second polymer calculated by the above formula (2) are shown in Table 1. Table 1 also shows the moisture absorption of the nanofiber layer calculated by the above formula (3). The mass ratio of the first polymer to the second polymer in the nanofiber layer-forming composition was the same as the mass ratio of the first polymer to the second polymer in the nanofiber layer formed using the nanofiber layer-forming composition.

[0085] [Usability evaluation] The nanofiber sheets produced in each example were evaluated by five expert panelists for usability before and after storage at high temperature and humidity. For evaluation of the nanofiber sheet before storage at high temperature and humidity, the nanofiber sheet immediately after production by the device 30 was used. To evaluate the nanofiber sheet after storage at high temperature and humidity, the nanofiber sheet immediately after production by the device 30 was packed in a breathable packaging material and left to stand in an incubator at 40°C and 90% RH (high temperature and humidity environment) for 24 hours.

[0086] The evaluation items for usability were transferability, compatibility, appearance, and wrinkles / bubbles. The expert panelists used the skin on the inside of their own forearms as the test site and evaluated the transferability of the nanofiber layer from the nanofiber sheet to the skin, how well the nanofiber layer fitted the skin after transfer, the appearance of the nanofiber layer attached to the skin, and whether any wrinkles or air bubbles had been mixed in the nanofiber layer attached to the skin.The evaluations were also conducted without applying any formulation before or after transferring the nanofiber layer. Five expert panelists evaluated each evaluation item on a five-point scale from 1 to 5 according to the item evaluation criteria described below, and based on the overall average score, evaluated the usability of the nanofiber sheet on a four-point scale from A to D according to the usability evaluation criteria described below. Table 1 shows the overall average scores for usability of the nanofiber sheets of each example before and after storage at high temperature and humidity, the evaluation results based on the scores, and the average scores for each evaluation item.

[0087] (Item evaluation criteria) 5 points...very good 4 points...good 3 points…average 2 points...bad 1 point...very bad

[0088] (Usability evaluation criteria) A: 4.5≦total average score≦5.0 B: 4.0≦total average score<4.5 C: 3.0≦total average score<4.0 D: Overall average score < 3.0

[0089] [Evaluation of moisture resistance of cast film] The moisture resistance of the cast film was evaluated as follows. 0.35 g of the polymer to be evaluated (a mixture of the first polymer and the second polymer in the blending ratio specified in each example) was dissolved in 4.65 g of ethanol to prepare 5 g of polymer solution. The polymer solution was prepared with a ratio of 7% polymer and 93% ethanol by mass. The polymer solution was placed in a 5 cm square plastic shell and dried at room temperature for 72 hours to evaporate the ethanol, producing a cast film. Next, the prepared cast film was left to stand in an incubator at 40°C and 90% RH (high temperature and humidity environment) for 24 hours. The weight change rate of the cast film before and after standing in the high temperature and humidity environment was calculated. Based on the weight change rate, the moisture absorption of the cast film was evaluated on a four-point scale (A to D) as follows. The evaluation results are shown in Table 1. A: 0%≦weight change rate≦5% B: 5% < weight change rate ≦ 10% C: 10% < weight change rate ≦ 15% D: 15% < weight change rate

[0090] [Table 1]

[0091] FIG. 4 is a graph prepared based on Table 1, showing the relationship between the proportion of the second polymer (horizontal axis) and the evaluation results of usability after storage at high temperature and humidity (vertical axis).

[0092] As shown in Table 1 and FIG. 4, when the proportion of the second polymer was 0.05 or more and 0.60 or less, the usability of the nanofiber sheet was excellent, rated C or better, both before and after storage at high temperature and humidity.

[0093] <<Test Example 2: Study of the second polymer, part 1>> For Examples 1 (same as Example 1 in Test Example 1), 13, and 14, nanofiber sheets were produced under the same production conditions as in Test Example 1 using compositions for forming nanofiber layers in which the blending ratio of the first polymer to the second polymer was the same but a different material was used for the second polymer.The usability of the nanofiber sheets before and after high temperature and humidity was evaluated using the same method as in Test Example 1. Further, the moisture resistance of a cast film formed in the same manner as in Test Example 1 using the first polymer and the second polymer in the blending ratio of each Example was evaluated in the same manner as in Test Example 1. In addition, as Comparative Example 1, a nanofiber sheet was produced using a composition for forming a nanofiber layer containing only the first polymer as the polymer, and the usability of the nanofiber sheet was evaluated.In addition, the moisture resistance of a cast film formed using only the first polymer was evaluated. Table 2 shows the overall average scores for usability of the nanofiber sheets of each Example and Comparative Example before and after storage at high temperature and humidity, the evaluation results based on the scores, the average scores for each evaluation item, and the evaluation results for the cast films.

[0094] [Preparation of nanofiber layer-forming composition] A mixture of the following first polymer, second polymer, and solvent was prepared as a nanofiber layer-forming composition for forming the nanofiber layer of the nanofiber sheets of Examples 1, 13, and 14. In preparing the mixture, the polymers were blended so that the mass ratio of the first polymer to the second polymer was 71.4:28.6. A mixture of the following first polymer and ethanol was prepared as a nanofiber layer forming composition for producing the nanofiber sheet of Comparative Example 1. The nanofiber layer forming composition did not contain a second polymer. (First polymer) A polyvinyl butyral resin (product name: S-LEC (registered trademark) BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated by the above formula (1) was 0.9%. (Second polymer) The following second polymers were used in each example. ((Example 1)) Vinyl acetate-vinylpyrrolidone copolymer (trade name: PVP / VA S63PLASDONE (registered trademark) S630, Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 16.8%. ((Example 13)) Vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer diethyl sulfate (trade name: Gafquat 734, Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 28.4%. ((Example 14)) Vinylcaprolactam·vinylpyrrolidone·dimethylaminopropyl methacrylamide·methacryloylaminopropyl lauryldimonium chloride copolymer (Aquastyle 300N, Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 19.8%. (solvent) Ethanol was used as a solvent, and was mixed in a proportion of 93% by mass in the composition for forming a nanofiber layer.

[0095] [Table 2]

[0096] <<Test Example 3: Study of the second polymer, part 2>> In Example 1 (same as Example 1 in Test Example 1) and Examples 15 to 17, nanofiber sheets were produced under the same production conditions as in Test Example 1 using compositions for forming nanofiber layers in which the second polymer was a vinyl acetate-vinylpyrrolidone copolymer with different composition ratios of vinylpyrrolidone (VP) and vinyl acetate (VA), and the blending ratio of the first polymer to the second polymer was the same. The usability of the nanofiber sheets before and after high temperature and humidity was evaluated using the same method as in Test Example 1. In addition, the moisture resistance of cast films formed using the first polymer and second polymer of each example was evaluated in the same manner as in Test Example 1. Table 3 shows the overall average scores for usability of the nanofiber sheets of each Example before and after storage at high temperature and humidity, the evaluation results based on the scores, the average scores for each evaluation item, and the evaluation results for the cast films.

[0097] [Preparation of nanofiber layer-forming composition] A mixture of the following first polymer, second polymer, and solvent was prepared as a composition for forming the nanofiber layer of the nanofiber sheets of Examples 1 and 15 to 17. In preparing the mixture, the polymers were blended so that the mass ratio of the first polymer to the second polymer was 71.4:28.6. (First polymer) A polyvinyl butyral resin (product name: S-LEC (registered trademark) BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated by the above formula (1) was 0.9%. (Second polymer) The following second polymers were used in each example. ((Example 1)) Vinyl acetate-vinylpyrrolidone copolymer (trade name: PLASDONE (registered trademark) S630 (composition ratio VP:VA=60:40), Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 16.8%. ((Example 15)) Vinyl acetate-vinylpyrrolidone copolymer (trade name: PVP / VA E735 (composition ratio VP:VA=70:30), Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 26.2%. ((Example 16)) Vinyl acetate-vinylpyrrolidone copolymer (trade name: PVP / VA S535 (composition ratio VP:VA=50:50), Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 14.6%. ((Example 17)) Vinyl acetate-vinylpyrrolidone copolymer (trade name: PVP / VA E335 (composition ratio VP:VA=30:70), Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 12.0%. (solvent) Ethanol was used as a solvent, and was mixed in a proportion of 93% by mass in the composition for forming a nanofiber layer.

[0098] [Table 3]

[0099] <<Test Example 4: Study of the second polymer, part 3>> For Example 1 (same as Example 1 in Test Example 1), Examples 18 to 21, and Comparative Examples 2 and 3, nanofiber sheets were produced under the same production conditions as in Test Example 1 using compositions for forming nanofiber layers in which the blending ratio of the first polymer to the second polymer was the same but different materials were used for the second polymer, and the usability of the nanofiber sheets before and after high temperature and humidity was evaluated using the same method as in Test Example 1. Furthermore, the moisture resistance of cast films formed in the same manner as in Test Example 1 using the first polymer and the second polymer of each of the Examples and Comparative Examples was evaluated in the same manner as in Test Example 1. The overall average scores for usability of the nanofiber layers formed from the nanofiber layer-forming compositions of each Example and Comparative Example before and after storage at high temperature and humidity, the evaluation results based thereon, the average scores for each evaluation item, and the evaluation results of the cast films are shown in Table 4. In Table 4, the "-" in the usability column indicates that the nanofiber layer dissolved and remained on the base layer, and the nanofiber layer was not sufficiently transferred to the skin, making it impossible to perform the evaluation.

[0100] [Preparation of nanofiber layer-forming composition] Mixtures of the first polymer, second polymer, and solvent shown below were prepared as nanofiber layer-forming compositions for producing the nanofiber sheets of Examples 1, 18 to 21, and Comparative Examples 2 and 3. In preparing the mixtures, the polymers were blended so that the mass ratio of the first polymer to the second polymer was 71.4:28.6. (First polymer) A polyvinyl butyral resin (product name: S-LEC (registered trademark) BH-3, Sekisui Chemical Co., Ltd.) was used as the first polymer. The moisture absorption of the polyvinyl butyral resin calculated by the above formula (1) was 0.9%. (Second polymer) The following second polymers were used in each of the Examples and Comparative Examples. ((Example 1)) Vinyl acetate-vinylpyrrolidone copolymer Vinyl acetate-vinylpyrrolidone copolymer (trade name: PLASDONE (registered trademark) S630, Ashland Japan Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 16.8%. ((Example 18)) Polyoxyethylene (20) polyoxypropylene (20) glycol (trade name: Pronon 124P, NOF Corporation) The moisture absorption of this polymer calculated by the above formula (1) was 8.5%. ((Example 19)) Polyoxyethylene (120) polyoxypropylene (40) glycol (trade name: Pronon 237P, NOF Corporation) The moisture absorption of this polymer calculated by the above formula (1) was 30.4%. ((Example 20)) Polyoxyethylene (196) polyoxypropylene (67) glycol (trade name: Pronon 407P, NOF Corporation) The moisture absorption of this polymer calculated by the above formula (1) was 30.9%. ((Example 21)) PEG-11 methyl ether dimethicone (trade name: Silicone KF6011, Shin-Etsu Chemical Co., Ltd.) The moisture absorption of this polymer calculated by the above formula (1) was 6.5%. (Comparative Example 2) Polyethylene glycol (trade name: PEG400, Wako Pure Chemical Industries, Ltd.) The polyethylene glycol is a polymer having an average molecular weight of 360 to 440. The moisture absorption of the polymer calculated by the above formula (1) was 45.6%. (Comparative Example 3) Polyethylene glycol (trade name: PEG1450, Sanyo Chemical Industries, Ltd.) The polyethylene glycol is a polymer with an average molecular weight of 1450. The moisture absorption of the polymer calculated by the above formula (1) was 42.0%. (solvent) Ethanol was used as a solvent, and was mixed in a proportion of 93% by mass in the composition for forming a nanofiber layer.

[0101] [Table 4]

[0102] In addition, the following primer liquid (preparation) formulation is disclosed as an example of a formulation that can be applied before or after the transfer of the nanofiber layer. <Primer liquid formulation> Pseudoceramide 1% by mass Glycerin fatty acid ester 0.34% by mass Cetyl alcohol 0.34% by mass Dimethylpolysiloxane 2% by mass Glycerin 10% by mass 1,3-butanediol 3% by mass Distearyldimonium chloride 0.4% by mass Polyoxyethylene sorbitan monostearate (20E.O.) 0.2% by mass Succinic acid 0.005% by mass Methyl parahydroxybenzoate 0.2% by mass The balance was made up with purified water to make the total 100% by mass. [Explanation of symbols]

[0103] 1...Nanofiber sheet 2...Base material layer 2a...Laminated surface (one side) 3...Nanofiber layer

Claims

1. A nanofiber sheet comprising a base layer and a nanofiber layer disposed on one surface of the base layer, the base layer being peeled off during use, and the nanofiber layer being attached to a target site, The nanofiber layer comprises: A first polymer having a moisture absorption of 1% or less in a high temperature and high humidity environment (when left standing for 24 hours at 40°C and 90% RH); A second polymer having a moisture absorption rate of more than 1% and not more than 40% when left standing for 24 hours under a high temperature and high humidity environment (40°C and 90% RH); Includes Nanofiber sheet.

2. When the mass of the first polymer in the nanofiber layer is M1 and the mass of the second polymer is M2, the value of M2 / (M1+M2) is 0.05 or more and 0.60 or less. The nanofiber sheet according to claim 1 .

3. The second polymer includes one or more polymers selected from polyvinylpyrrolidone, copolymers of polyvinylpyrrolidone, polyalkylene glycols, and copolymers containing a silicone structure. The nanofiber sheet according to claim 1 or 2.

4. The second polymer includes one or more polymers selected from vinyl acetate-vinylpyrrolidone copolymer, vinylpyrrolidone-dimethylaminoethyl methacrylate copolymer diethyl sulfate, vinylcaprolactam-vinylpyrrolidone-dimethylaminopropyl methacrylamide-methacryloylaminopropyl lauryldimonium chloride copolymer, polyoxyethylene polyoxypropylene glycol, and PEG-11 methyl ether dimethicone. The nanofiber sheet according to claim 3 .

5. The first polymer is one or more polymers selected from the group consisting of polyvinyl butyral resin, polyurethane resin, and polylactic acid. The nanofiber sheet according to claim 1 or 2.

6. The base layer is made of fibers having a standard moisture regain of 8% or more. The nanofiber sheet according to claim 1 or 2.

7. The target site for attachment is human skin. The nanofiber sheet according to claim 1 or 2.

8. The nanofiber sheet according to claim 1 or 2, a preparation that is applied to the target site before or after the nanofiber layer is attached to the skin when the nanofiber sheet is used; A skin protection kit comprising:

9. A method for producing a nanofiber sheet comprising: a base layer; and a nanofiber layer disposed on one surface of the base layer; the base layer is peeled off during use, and the nanofiber layer is attached to a target site, the method comprising the steps of: The method includes a step of applying a composition for forming a nanofiber layer to one surface of the base layer by an electrospinning method to form the nanofiber layer, The nanofiber layer forming composition is A first polymer having a moisture absorption of 1% or less in a high temperature and high humidity environment (when left standing for 24 hours at 40°C and 90% RH); A second polymer having a moisture absorption of more than 1% and not more than 40% in a high temperature and high humidity environment (when left standing for 24 hours at 40°C and 90% RH); One or more selected from monohydric alcohols and ketones; Includes A method for manufacturing a nanofiber sheet.